Polymeric composite nanofiber membrane as well as preparation method and application thereof

By using electrospinning technology of ZnO nanoparticles and polyacrylonitrile in medical masks, nanofiber membranes are prepared, and combined with lamination technology to construct nanopower generation layer and hydrophobic support layer, the problems of the mask's mechanical strength and hydrophobic interface are solved, and the problem of the mask is improved Filtration effect and wear comfort, and real-time physiological signal monitoring is achieved.

CN119116517AActive Publication Date: 2024-12-13NINGBO UNIV

Patent Information

Application Number
CN202411037509.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2024-12-13
Estimated Expiration
2044-07-31

AI Technical Summary

Technical Problem

The mechanical strength of the polymerized composite nanofiber membrane of existing medical masks is poor and the hydrophobic interface is unstable, which affects the filtration effect and wear comfort of the mask, especially the water vapor exhaled during long-term wear, which leads to static electricity consumption and water droplet aggregation problems.

Method used

The nanofiber membrane is prepared by electrospinning technology combining ZnO nanoparticles and polyacrylonitrile (PAN), and the nanoelectric power generation layer and hydrophobic support layer of sandwich structure are constructed through the lamination process to form a polymer composite nanofiber membrane and combine hydrophilic support. and micro-sodium electrode layer to improve mechanical strength and hydrophobic properties.

Benefits of technology

It realizes a high mechanical strength and stable hydrophobic interface, improves the filtering effect and wear comfort of the mask, and monitors physiological signals in real time through TENG technology to provide support for health monitoring and disease warning.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119116517A_ABST
    Figure CN119116517A_ABST
Patent Text Reader

Abstract

The invention provides a polymeric composite nanofiber membrane and a preparation method and application thereof.The polymeric composite nanofiber membrane comprises a hydrophilic supporting layer, a micro-sodium electrode layer and a nano power generation layer, the hydrophobic supporting layer, the micro-sodium electrode layer and the hydrophilic supporting layer are made of polyacrylonitrile and cellulose acetate, the micro-nano electrode layer is made of a copper-plated polyester spinning electrode, and the nano power generation layer is made of cellulose acetate. The nano power generation layer is prepared by compounding polyvinylidene fluoride and a zinc oxide nano material through an electrostatic spinning technology, the hydrophilic support layer is prepared by compounding polyacrylonitrile and zinc oxide, and the hydrophobic support layer is a polytetrafluoroethylene material layer; the preparation method comprises the following steps: sequentially superposing all the layers of materials, and preparing the multi-layer polymeric composite nanofiber membrane through a lamination process. The application of the polymer composite nanofiber membrane comprises application of the polymer composite nanofiber membrane in a mask, so that the environment in the mask is improved, and the durability and wearing comfort of the mask are improved. The polymeric composite nanofiber membrane provided by the invention has reliable mechanical strength and hydrophobic interface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanofiber membrane preparation, and in particular to a polymer composite nanofiber membrane and a preparation method and application thereof. Background Art

[0002] Current medical masks are usually made of three layers of polypropylene (PP) non-woven fabric, including two inner and outer layers of non-woven fabric and a middle meltblown fabric. These masks mainly rely on mechanical blocking effects such as Brownian diffusion, interception, inertial collision and gravity sedimentation to capture and filter particles in the air through fiber mesh. However, this fiber mesh filtration method has poor filtering effect on submicron particles. Although reducing the filter mesh aperture and increasing the fiber density can improve the filtration effect, it will also significantly increase the air resistance. In order to overcome the limitations of traditional fiber filter materials, some new adsorbent materials, such as electret filter materials and composite filter materials, have received widespread attention. Electret air filter materials show great application prospects due to their advantages such as high efficiency, low resistance, energy saving and antibacterial. In addition to the action mechanisms of traditional filter materials such as inertial collision, interception and diffusion, these materials also capture air particles through Coulomb force. When air particles pass through the filter, the electrostatic force can not only effectively attract charged particles, but also capture polarized neutral particles through the electrostatic induction effect, thereby improving the filtration efficiency. The relatively sparse structure ensures minimal airflow resistance without reducing efficiency. For example, the particle protection masks produced by 3M in the United States use electrostatic fibers, which can effectively filter ultrafine dust. The meltblown cloth has a small pore size (2μm) and is charged after electret treatment. It can block charged virus particles through electrostatic adsorption and reduce the risk of infection. However, when wearing a mask for a long time, the exhaled water vapor will accelerate the consumption of static electricity, reduce the adsorption efficiency, and increase the risk of infection. In addition, the accumulation of exhaled water vapor in the mask leads to a humid environment. When the saturated humidity airflow passes through, the condensed water easily attenuates the static electricity of the filter.

[0003] Triboelectric nanogenerators (TENGs) use friction electrification and electrostatic induction effects to collect external mechanical energy and convert it into electrical energy. In recent years, TENG research in the field of self-powered sensors has made significant progress, especially in health monitoring and disease early warning, and has great application prospects. The stability and reliability of TENG self-powered sensors are crucial, which requires the TENG power generation layer in the mask to have reliable mechanical strength and hydrophobic interface.

[0004] However, the long-term contact between the skin and the water droplets formed by the condensation of water vapor exhaled by the human body on the inner surface of the mask will lead to the accumulation of water at the mask filter interface, increase the breathing resistance, and reduce the static electricity of the filter layer, thus affecting the performance of the sensor. Therefore, improving the internal environment of the mask is of great significance to improving the durability and wearing comfort of the mask and TENG. It is urgent to design a polymer composite nanofiber membrane containing a friction nanogenerator and apply it to the mask to provide reliable mechanical strength and hydrophobic interface. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a polymer composite nanofiber membrane, thereby solving the problems of poor mechanical strength and unstable hydrophobic interface of the polymer composite nanofiber membrane in the prior art.

[0006] In order to solve the above problems, the present invention provides a method for preparing a polymer composite nanofiber membrane, which is characterized by comprising the following steps:

[0007] S1: Preparation of ZnO nanoparticles: NaOH is added dropwise to a zinc acetate solution to form an emulsion suspension, the emulsion suspension is allowed to stand until the emulsion suspension is precipitated, the precipitate is extracted and washed to neutrality, and then the precipitate is heated to obtain ZnO nanoparticles;

[0008] S2: Preparation of ZnO / PAN nanofiber membrane: dissolving polyacrylonitrile in N,N-dimethylformamide solution to obtain polyacrylonitrile solution, dissolving ZnO nanoparticles in N,N-dimethylformamide solution, stirring to obtain ZnO nanoparticle solution, then mixing the polyacrylonitrile solution and the ZnO nanoparticle solution to obtain a ZnO suspension solution, using the ZnO suspension solution as a spinning solution for electrospinning, and after spinning, curing the obtained spinning membrane and further removing the solvent to obtain a ZnO / PAN nanofiber membrane;

[0009] S3: Preparation of nano power generation layer: adding the ZnO nanoparticles to the PVDF / DMF solution and stirring, further adding polyethylene glycol to the stirring solution to obtain an electrostatic spray solution, using the ZnO / PAN nanofiber membrane prepared in step S2 as a receiving substrate, electrostatically spraying the electrostatic spray solution on the receiving substrate to obtain a nano-microsphere layer, and after the electrostatic spraying is completed, replacing the electrostatic spray solution with a ZnO / PVDF electrospinning precursor solution, and performing electrostatic spinning to obtain a nano power generation layer with a sandwich structure;

[0010] S4: Preparation of a hydrophilic support layer: PAN or PDMS powder is dissolved in a solvent, cellulose acetate is added and mixed, and then a membrane is formed by electrospinning to obtain a hydrophilic support layer;

[0011] Preparation of the hydrophobic support layer: dissolving polytetrafluoroethylene powder in a solvent and preparing it into a thin film by a flat coating method, a tape casting method or a solution casting method to obtain a hydrophobic support layer;

[0012] S5: Lamination to prepare composite membrane: stack the hydrophilic support layer, micro-sodium electrode layer, nano-power generation layer, hydrophobic support layer and micro-sodium electrode layer in this order and add adhesive, and prepare a polymer composite nanofiber membrane after hot pressing and lamination; the micro-sodium electrode layer is an electrode layer with micro-nano electrodes.

[0013] In the above preparation method of the present invention, a viscous electrostatic guide layer and a hydrophobic PTFE and macroporous PAN layer are superimposed on the PAN / ZnO nanofiber membrane by continuous electrostatic spraying / spinning technology, and finally a full nanofiber fabric is prepared. Among them, the PAN layer is close to the skin, and the hydrophilicity of the fabric shows an increasing trend from the inside to the outside. On the contrary, the pore size gradually decreases. Under the synergistic effect of the static pressure applied by the skin pores, the excellent hygroscopicity and capillary force of the HPAN / ZnO fiber membrane, the excellent moisture absorption and directional perspiration functions are achieved. Compared with the prior art, a stronger hydrophobic interface is constructed, and a polymer composite nanofiber membrane with high mechanical strength is provided;

[0014] In a possible embodiment, in step S1, the step of adding NaOH dropwise to the zinc acetate solution comprises: adding NaOH with a concentration of 3M dropwise to the zinc acetate solution at a temperature of 85-95°C; the pH of the emulsion suspension is 12.5-13.5; the method for preparing the zinc acetate solution comprises: dissolving zinc acetate dihydrate in deionized water at room temperature at a speed of 500-1000 rpm for 60 minutes to obtain a zinc acetate solution, and the mass ratio of the zinc acetate dihydrate to the deionized water is 5:(20-30).

[0015] In a possible implementation, in the step S1, the condition for heating the precipitate is: heating the precipitate at a temperature of 100-110° C. for 60 minutes.

[0016] In a possible embodiment, in step S2, in the polyacrylonitrile solution, the mass ratio of polyacrylonitrile to N,N-dimethylformamide solution is (3-4):(20-30); the stirring conditions for obtaining the ZnO nanoparticle solution after stirring are: stirring at a speed of 1000 rpm at a temperature of 60°C for 100-140 minutes, and the mass ratio of ZnO nanoparticles to N,N-dimethylformamide solution is (0.3-0.4):(4-6).

[0017] In a possible embodiment, in step S2, the conditions for mixing and stirring the polyacrylonitrile solution and the ZnO nanoparticle solution are: stirring at a temperature of 80°C and a speed of 400-600rpm for 360 minutes; the conditions for the electrospinning include: a space of 13cm between the tip of the positive terminal and the negative terminal, an injection speed of 10uL / minute, a voltage of 18-19kV, and a needle tip distance of 13-15cm from the receiver; the conditions for further removing the solvent after the solidification include: placing the spinning membrane in a 60°C vacuum drying oven overnight after the spinning process is completed to complete the curing and drying, and then placing the spinning membrane in a 60°C forced air drying oven for 12 hours to accelerate the volatilization of the solvent and remove the solvent.

[0018] In a possible embodiment, in the step S2, after obtaining the ZnO / PAN nanofiber membrane, the step of hydrolyzing the ZnO / PAN nanofiber membrane is further included, including: hydrolyzing the ZnO / PAN nanofiber membrane in a NaOH alcohol / water mixed solution for 0.5-2h to obtain a hydrophilic HPAN / ZnO nanofiber membrane.

[0019] The hydrophilicity of the PAN / ZnO fiber membrane was improved by hydrolyzing the ZnO / PAN nanofiber membrane in a NaOH alcohol / water mixed solution to obtain a hydrophilic HPAN / ZnO nanofiber membrane, which was used as a collection matrix in the subsequent preparation process.

[0020] In a possible embodiment, in the step S3, the stirring condition is stirring at a temperature of 60-80°C and a speed of 1000rpm for 60 minutes; the conditions for the electrostatic spraying are: electrostatic spraying at a temperature of 25°C and a humidity of 50%, and the injection speed is 10μL / min, the voltage is 16-18kV, and the needle is 13-15cm away from the receiver; after obtaining the sandwich structure nano power generation layer, it also includes the step of placing the nano power generation layer in a 60°C vacuum drying oven overnight to complete curing and drying and remove the solvent contained in the composite film; in the ZnO / PVDF electrospinning precursor solution, the amount of ZnO added is 0.5% to 2wt% of the total mass of the solvent.

[0021] In a possible embodiment, in the step S4, in the preparation of the hydrophilic support layer, the solvent is N-methylpyrrolidone solvent, and the amount of cellulose acetate added is 0.5wt% to 2wt% of the solvent; and after the mixing is implemented, it also includes: magnetically stirring the mixture in a 70°C water bath for 6 hours, and then placing it in a bath ultrasonicator for 1 hour to eliminate bubbles, and then casting the mixture on a smooth polytetrafluoroethylene culture dish, and drying it in an oven at 70°C for 1 hour; the conditions for preparing the cast film by the hot pressing method are: applying a pressure of 10MPa at 90-100°C and hot pressing it for 2 minutes.

[0022] The second technical problem to be solved by the present invention is to provide a polymer composite nanofiber membrane to solve the problems of general mechanical strength and weak hydrophobic interface of conventional composite nanofiber membranes.

[0023] A polymer composite nanofiber membrane, which is prepared by the preparation method of the polymer composite nanofiber membrane, and the polymer composite nanofiber membrane includes a hydrophilic support layer, a micro-sodium electrode layer, a nano power generation layer, a hydrophobic support layer, and a micro-sodium electrode layer arranged in sequence from bottom to top. The polymer composite nanofiber membrane is prepared by stacking the above layers in sequence through a lamination process.

[0024] A polymer composite nanofiber membrane in the present invention is constructed into a nanofiber fabric-based moisture absorption and drainage layer through continuous electrospinning / spray spinning technology, which is used to collect external mechanical energy and monitor self-powered human motion signals. The fabric is composed of two fiber membranes with opposite wettability (hydrophilic and hydrophobic), wherein the components and functions of each layer include:

[0025] 1. Micro-nano electrode layer (Cu-plated polyester spinning electrode): This layer is a nanofiber membrane with silver and copper plated on the surface, providing excellent conductivity. Generally speaking, the micro-sodium electrode layer is copper- and silver-plated polyester, or other materials with similar functions, which can play the role of utilizing airflow vibration energy to generate AC power.

[0026] 2. Nano power generation layer (sandwich structure nano power generation layer TENG): It is made of polyvinylidene fluoride (PVDF) and zinc oxide (ZnO) nanomaterials and prepared by electrospinning technology. It has good piezoelectric properties and can convert the mechanical energy generated by respiratory airflow energy and facial movements into electrical energy. The layer structure includes 3 layers, including layer 1, layer 2, and layer 3 from bottom to top. Layer 1 is a PVDF / ZnO nanofiber layer, layer 2 is a PVDF+ZnO nanosphere layer, and layer 3 is a PAN+ZnO nanofiber layer.

[0027] 3. Hydrophilic support layer (PAN+CA): Polyacrylonitrile (PAN) and cellulose acetate CA are composited to provide mechanical support and have a certain hydrophilicity to help guide and disperse water vapor.

[0028] 4. Hydrophobic support layer (PTFE): Polytetrafluoroethylene (PTFE) material layer, PTFE powder is dissolved in a suitable solvent and prepared into a film by solution casting. It has good hydrophobicity, prevents water droplets from gathering, and improves breathing comfort.

[0029] Another technical problem to be solved by the present invention is to provide an application of a polymer composite nanofiber membrane, which includes applying the polymer composite nanofiber membrane to a mask.

[0030] In the application of a polymer composite nanofiber membrane in the present invention, since the polymer composite nanofiber membrane adopts a textile electrostatic flow guide net and is laminated with a nanofiber composite membrane to obtain a sandwich structured nano power generation composite membrane, after it is applied to a mask, the multi-layer composite nanofiber mask is worn on the face, and the wearer's breathing and physiological signals are monitored in real time through the TENG technology, and mechanical energy is converted into electrical energy. The waterproof protective layer and the hydrophobic support layer effectively prevent water droplets from gathering and improve wearing comfort. The nano power generation layer and the micro-nano electrode layer ensure the stability and reliability of the sensor. Through the technical solution of the present invention, not only the filtering effect and wearing comfort of the mask are improved, but also real-time physiological signal monitoring is realized, which provides strong support for health monitoring and disease early warning. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a structural diagram of the polymer composite nanofiber membrane;

[0032] Figure 2 Schematic diagram of the composite structure of the nano power generation layer;

[0033] Figure 3 This is a schematic diagram of the energy management circuit of the nano power generation layer;

[0034] Figure 4 A graph showing the charging of different capacitors by the nano-generating layer;

[0035] Figure 5 is the open circuit output voltage of the nano power generation layer under an alternating pressure of 50 Pa, wherein M5 is the nano power generation layer structure in the present invention;

[0036] Figure 6 The piezoelectric coefficient test diagram of membrane layers with different structures;

[0037] Figure 7 is the β-crystal content of PVDF fiber membrane;

[0038] Figure 8The microscopic surface morphology image (magnification ×400) and the scanning electron microscope image (5mm×100) of the micro-nano electrode layer in the present invention;

[0039] Fig. 9 The microscopic morphology (×100) and scanning electron microscope morphology (×5K) of the surface of the PAN / ZNO electrospun fiber membrane in the present invention;

[0040] Fig.10 A cross-sectional view of a sandwich structure composite film of a nano-power generation layer in the present invention;

[0041] Fig.11 It is a schematic diagram of applying the polymer composite nanofiber membrane of the present invention to a mask;

[0042] Figure 2 , 10 In the figure, layerI: layer 1: PAN nanofiber hydrophilic layer, layerII: layer 2: PVDF+ZnO nanosphere layer, layerIII: layer 3: PAN+ZnO nanofiber layer. DETAILED DESCRIPTION

[0043] First, those skilled in the art should understand that these implementations are only used to explain the technical principles of the embodiments of the present application, and are not intended to limit the protection scope of the embodiments of the present application. Those skilled in the art can make adjustments to them as needed to adapt to specific application scenarios.

[0044] The present invention provides a method for preparing a polymer composite nanofiber membrane, which is characterized by comprising the following steps:

[0045] S1: Preparation of ZnO nanoparticles: NaOH is added dropwise to a zinc acetate solution to form an emulsion suspension, the emulsion suspension is allowed to stand until the emulsion suspension is precipitated, the precipitate is extracted and washed to neutrality, and then the precipitate is heated to obtain ZnO nanoparticles;

[0046] S2: Preparation of ZnO / PAN nanofiber membrane: polyacrylonitrile is dissolved in N,N-dimethylformamide solution to obtain polyacrylonitrile solution, ZnO nanoparticles are dissolved in N,N-dimethylformamide solution, and ZnO nanoparticle solution is obtained after stirring, and then the polyacrylonitrile solution and ZnO nanoparticle solution are mixed and stirred to obtain ZnO suspension solution, and the ZnO suspension solution is used as a spinning solution for electrospinning, and after spinning, the obtained spinning membrane is cured and cleaned, and the solvent is further removed to obtain ZnO / PAN nanofiber membrane (attached Figure 1 Named as nanofiber layer 1);

[0047] S3: Preparation of nano power generation layer: adding the ZnO nanoparticles to the PVDF / DMF solution and stirring, further adding polyethylene glycol to the stirring solution to obtain an electrostatic spray solution, using the ZnO / PAN nanofiber membrane prepared in step S2 as a receiving substrate, and electrostatically spraying the electrostatic spray solution on the receiving substrate to obtain a nanosphere layer (attached Figure 1 After the electrostatic spraying is completed, the electrostatic spraying solution is replaced with a ZnO / PVDF electrospinning precursor solution for electrostatic spinning. Figure 1 The nanofiber layer 1 is spun to obtain a nano-power generation layer with a sandwich structure;

[0048] S4: Preparation of a hydrophilic support layer: PAN or PDMS powder is dissolved in a solvent, cellulose acetate is added and mixed, and then a membrane is formed by electrospinning to obtain a hydrophilic support layer;

[0049] Preparation of the hydrophobic support layer: dissolving polytetrafluoroethylene powder in a solvent and preparing it into a thin film by a flat coating method, a tape casting method or a solution casting method to obtain a hydrophobic support layer;

[0050] S5: Lamination to prepare composite membrane: stack the hydrophilic support layer, the micro-sodium electrode layer, the nano-power generation layer, the hydrophobic support layer, and the micro-sodium electrode layer in order and add an adhesive, and the structure is as follows: Figure 1 As shown, after hot pressing and compounding, a polymer composite nanofiber membrane is prepared; the micro-sodium electrode layer is an electrode layer with micro-nano electrodes. Generally speaking, the micro-sodium electrode layer is copper- and silver-plated polyester, and can also be other materials with similar functions, which can play the role of utilizing airflow vibration energy to generate AC power.

[0051] As a preferred solution, in step S1, the step of adding NaOH dropwise to the zinc acetate solution comprises: adding NaOH with a concentration of 3M dropwise to the zinc acetate solution at a temperature of 85-95°C; the pH of the emulsion suspension is 12.5-13.5; the method for preparing the zinc acetate solution comprises: dissolving zinc acetate dihydrate in deionized water at room temperature at a speed of 500-1000 rpm for 60 minutes to obtain a zinc acetate solution, and the mass ratio of the zinc acetate dihydrate to the deionized water is 5:(20-30).

[0052] As a preferred solution, in step S1, the condition for heating the precipitate is: heating the precipitate at a temperature of 100-110° C. for 60 minutes.

[0053] As a preferred embodiment, in step S2, in the polyacrylonitrile solution, the mass ratio of polyacrylonitrile to N,N-dimethylformamide solution is (3-4):(20-30); the stirring conditions for obtaining the ZnO nanoparticle solution after stirring are: stirring at a speed of 1000 rpm at a temperature of 60°C for 100-140 minutes, and the mass ratio of ZnO nanoparticles to N,N-dimethylformamide solution is (0.3-0.4):(4-6).

[0054] As a preferred scheme, in the step S2, the conditions for mixing and stirring the polyacrylonitrile solution and the ZnO nanoparticle solution are: stirring at a speed of 400-600rpm for 360 minutes at a temperature of 80°C; the conditions for the electrospinning include: a space of 13cm between the tip of the positive terminal and the negative terminal, an injection speed of 10uL / minute, a voltage of 18-19kV, and a needle tip distance of 13-15cm from the receiver; the conditions for further removing the solvent after the solidification include: placing the spinning membrane in a 60°C vacuum drying oven overnight after the spinning process is completed to complete the curing and drying, and then placing the spinning membrane in a 60°C forced air drying oven for 12 hours to accelerate the volatilization of the solvent and remove the solvent.

[0055] As a preferred scheme, in the step S2, after obtaining the ZnO / PAN nanofiber membrane, the step of hydrolyzing the ZnO / PAN nanofiber membrane is also included, including: hydrolyzing the ZnO / PAN nanofiber membrane in a NaOH alcohol / water mixed solution for 0.5-2h to obtain a hydrophilic HPAN / ZnO nanofiber membrane.

[0056] As a preferred scheme, in the step S3, the stirring condition is stirring at a temperature of 60-80°C and a speed of 1000rpm for 60 minutes; the conditions for the electrostatic spraying are: electrostatic spraying at a temperature of 25°C and a humidity of 50%, and the injection speed is 10μL / min, the voltage is 16-18kV, and the needle is 13-15cm away from the receiver; after obtaining the sandwich structure nano power generation layer, it also includes the step of placing the nano power generation layer in a 60°C vacuum drying oven overnight to complete curing and drying and remove the solvent contained in the composite film; in the ZnO / PVDF electrospinning precursor solution, the amount of ZnO added is 0.5% to 2wt% of the total mass of the solvent.

[0057] As a preferred embodiment, in the step S4, in the preparation of the hydrophilic support layer, the solvent is N-methylpyrrolidone solvent, and the amount of cellulose acetate added is 0.5wt% to 2wt% of the solvent; and after the mixing is implemented, it also includes: magnetically stirring the mixture in a 70°C water bath for 6 hours, and then placing it in a bath ultrasonicator for 1 hour to eliminate bubbles, and then casting the mixture on a smooth polytetrafluoroethylene culture dish and drying it in an oven at 70°C for 1 hour; the conditions for preparing the cast film by the hot pressing method are: applying a pressure of 10MPa at 90-100°C and hot pressing it for 2 minutes.

[0058] The present invention also provides a polymer composite nanofiber membrane, the polymer composite nanofiber membrane is prepared by the polymer composite nanofiber membrane preparation method, and the polymer composite nanofiber membrane comprises a hydrophilic support layer, a micro-sodium electrode layer, a nano power generation layer, a hydrophobic support layer, and a micro-sodium electrode layer arranged in sequence from bottom to top, and the polymer composite nanofiber membrane is prepared by stacking the above layers in sequence through a lamination process;

[0059] like Figure 1 As shown, the specific structure stacking order is, from bottom to top, a hydrophilic support layer, a micro-sodium electrode layer, a nano-power generation layer (including, from bottom to top, a nanofiber layer 3, a nano-microsphere layer 2, and a nanofiber layer 1), a hydrophobic support layer, and a micro-sodium electrode layer;

[0060] The present invention also provides an application of the polymer composite nanofiber membrane, which includes applying the polymer composite nanofiber membrane to a mask.

[0061] The following is a description of the above technical solution of the present invention in combination with actual data and tests:

[0062] In the following embodiments, the raw materials and equipment involved include but are not limited to:

[0063] 1. Materials: polymers: polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyethylene glycol (PEG), polydimethylsiloxane (PDMS), polyethersulfone (PSf) and other polymers, nano zinc oxide (ZnO nws), zinc acetate dihydrate (Zn(Ac)2·2(H2O)), zinc nitrate hexahydrate (Zn(NO3)2·6(H2O))

[0064] Solvents: deionized water, methanol, N-methylpyrrolidone (NMP), N-dimethylacetamide (DMF);

[0065] 2. Equipment: high-speed stirrer, ultrasonic disperser, electrospinning device, aluminum foil collecting plate, hot press.

[0066] Embodiment 1:

[0067] This embodiment provides a polymer composite nanofiber membrane and its preparation method and application. Through continuous electrospinning / spray spinning technology, a nanofiber fabric-based moisture absorption and drainage layer is constructed, which is used to collect external mechanical energy and monitor self-powered human motion signals. The fabric is composed of two fiber membranes with opposite wettability (hydrophilic and hydrophobic). The specific structure is as shown in the attached figure. Figure 1 and Fig.11 Shown on the right.

[0068] The structure of the polymer composite nanofiber membrane in this embodiment is as follows Figure 1 as well as Fig.11 As shown on the right side of the figure, the nano power generation layer includes a nanofiber layer 1, a nanosphere layer 2, and a nanofiber layer 3. The hydrophobic support layer is composited with the nano power generation layer by hot pressing to form the TENG structure of the present invention. The polymer composite nanofiber membrane of the present invention includes:

[0069] 1. Micro-nano electrode layer (Cu-plated polyester spinning electrode): This layer is a nanofiber membrane with silver and copper plated on the surface, providing excellent conductive properties;

[0070] 2. Nano power generation layer (sandwich structure nano power generation layer TENG): It is made of polyvinylidene fluoride (PVDF) and zinc oxide (ZnO) nanomaterials, prepared by electrospinning technology, and has good piezoelectric properties. It can convert the mechanical energy generated by breathing airflow and facial movements into electrical energy. The structure of this layer is as follows: Figure 2 As shown, a cross-sectional view of the TENG structure of the present invention is shown, including the specific composition and arrangement of each layer. Figure 2 It is a TENG composite structure, in which layer 1 is a PVDF / ZnO nanofiber layer, layer 2 is a PVDF+ZnO nanosphere layer, and layer 3 is a PAN+ZnO nanofiber layer; Fig.10 This is the cross-sectional view of the sandwich structure composite film of the nano-power generation layer (1mm×150);

[0071] Figure 6 This is a test diagram of the piezoelectric coefficient of the nano power generation layer prepared in Example 1. Figure 6 It shows that the piezoelectric coefficient of the sandwich composite nano-power generation layer M5 of the present invention can reach 27.8 pm / V;

[0072] Figure 3 This is a schematic diagram of the energy management circuit of the nano power generation layer;

[0073] Figure 8 The microscopic surface morphology (magnification ×400) and scanning electron microscope image (5mm×100) of the micro-nano electrode layer prepared in this embodiment are shown in FIG.

[0074] Fig. 9The microscopic morphology (×100) and scanning electron microscope morphology (×5K) of the surface of the PAN / ZNO electrospun fiber membrane (layer 3) in the micro-nano electrode layer prepared in this embodiment;

[0075] 3. Hydrophilic support layer (PAN+CA): Polyacrylonitrile (PAN) and cellulose acetate CA are composited to provide mechanical support and have a certain degree of hydrophilicity to help guide and disperse water vapor;

[0076] 4. Hydrophobic support layer (PTFE): Polytetrafluoroethylene (PTFE) material layer, PTFE powder is dissolved in a suitable solvent and prepared into a film by solution casting. It has good hydrophobicity, prevents water droplets from gathering, and improves breathing comfort.

[0077] Lamination and composite: The above layers are stacked in sequence to prepare a multi-layer composite nanofiber mask through a lamination process.

[0078] The preparation method of the polymer composite nanofiber membrane comprises:

[0079] S1: Synthesis of ZnO nanoparticles: 5 g of zinc acetate dihydrate was dissolved in 25 ml of deionized water at 600 rpm using a magnetic stirrer at room temperature (27°C) for 60 minutes; then, 12 ml of NaOH 3M was added dropwise to the zinc acetate solution at 90°C to form an emulsion suspension with a pH of about 13, which was then allowed to stand until precipitation. The sediment was then washed until the pH was neutral; subsequently, the obtained sediment was heated at 100°C for 60 minutes, and the formed ZnO nanoparticles were used for the next process.

[0080] S2: Preparation of ZnO / PAN nanofiber membrane: The synthesis of PAN@ZnO nanofibers was performed by electrospinning. The ZnO suspension solution was prepared by weighing 3.2g PAN (polyacrylonitrile) and dissolving it in 20g DMF, and weighing 0.32g ZnO and dissolving it in 5g DMF; then stirring at 1000rpm for 120 minutes at a temperature of 60°C. The above two solutions were mixed, and then stirred at 500rpm for 360 minutes at a temperature of 80°C to prepare the PAN / ZnO spinning solution, and the composite solution was injected into 4 5ml syringe pumps, each with 2.5ml. Then a 21G size syringe needle was installed on the syringe and connected horizontally to the positive terminal, so that the positive terminal tip (needle) and the aluminum collector plate (negative terminal) had a space of 13cm. The injection rate was 10uL / min, the voltage was 18kV~19kV, and the needle was 13~15cm away from the receiver. After the spinning process is completed, the spinning membrane is placed in a 60°C vacuum drying oven overnight to complete the curing and drying and remove the solvent contained in the fiber membrane, and then placed in a 60°C forced air drying oven for 12 hours to accelerate the volatilization of the solvent to obtain a PAN / ZnO spinning fiber membrane as a nano-power generation layer 3; then it is hydrolyzed in a NaOH alcohol / water mixed solution for 0.5h to obtain a hydrophilic HPAN / ZnO nanofiber membrane (i.e., the above Figure 2 / 10 layer 3), and use this fiber membrane as a collecting matrix in the subsequent preparation process;

[0081] S3: Preparation of nanosphere layer: Preparation of sandwich structure TENG by co-spinning method: ZnO nanoparticles were mixed into (9wt%~11wt%) PVDF / DMF solution and stirred at 70℃ and 1000rpm for 60 min, PEG (1wt%) was added and then the solution was used as PVDF / ZnO electrostatic spray solution, after which the synthesized layer 3 (PAN / ZnO fiber membrane) was used as the receiving substrate and electrostatically sprayed at 25℃ and 50% humidity to prepare the microsphere layer (i.e., the above Figure 2 / 10 layer 2), the injection speed is 10μL / min, the voltage is 16kV~18kV, the needle is 13~15cm away from the receiver, and immediately after the electrostatic spray is completed, it is replaced with 14wt% ZnO / PVDF electrospinning precursor solution (the amount of ZnO added is 1wt%), and the above Figure 2 / 10 middle layer 1 is spun, and after completion, the spun membrane is placed in a 60°C vacuum drying oven overnight to complete curing and drying and remove the solvent contained in the composite membrane.

[0082] S4: Preparation of hydrophilic support layer by hot pressing: The support layer nanocomposite was prepared into a thin film by solution casting. An appropriate amount of PAN or PDMS powder was dissolved in N-methylpyrrolidone (NMP) solvent. At the same time, different amounts of CA (1wt%) were also dissolved in the solvent. The mixture was magnetically stirred in a 70°C water bath for 6 hours. It was then placed in a bath sonicator for 1 hour to eliminate bubbles to improve the dispersion of GO and eliminate bubbles. The mixture was cast on a smooth polytetrafluoroethylene petri dish and dried in an oven at 70°C for 1 hour to ensure the removal of the solvent. The solvent cast membrane was then further processed by hot pressing, and the membrane was hot pressed for 2 minutes under a pressure of 10MPa at 90°C.

[0083] Preparation of the hydrophobic support layer: dissolving polytetrafluoroethylene powder in a solvent and preparing it into a thin film by a flat coating method, a tape casting method or a solution casting method to obtain a hydrophobic support layer;

[0084] S5: Lamination to prepare composite membrane: A textile electrostatic guide net is used to be laminated with a nanofiber composite membrane to obtain a sandwich-structured nano-power generation composite membrane, which is stacked in the order of the hydrophilic support layer, micro-sodium electrode layer, layer 3 of the nano-power generation layer, layer 2 of the nano-power generation layer, layer 1 of the nano-power generation layer, the hydrophobic support layer, and micro-sodium electrode layer, and an adhesive is added.

[0085] This embodiment also provides the application of the composite film on a mask, and its structure is as follows Fig.11 As shown, the multi-layer composite nanofiber mask of this embodiment is worn on the face, and the wearer's breathing and physiological signals are monitored in real time through the TENG technology, and mechanical energy is converted into electrical energy. The waterproof protective layer and the hydrophobic support layer effectively prevent water droplets from gathering and improve wearing comfort. The nano-power generation layer and the micro-nano electrode layer ensure the stability and reliability of the sensor. Through the technical solution of the present invention, not only the filtering effect and wearing comfort of the mask are improved, but also real-time physiological signal monitoring is realized, which provides strong support for health monitoring and disease early warning.

[0086] The polymer composite nanofiber membrane prepared in Example 1 is applied to the charging of a capacitor. Figure 4 The curve diagram of the nano-power generation layer in Example 1 charging different capacitors, Figure 5 This is the open circuit output voltage under 50Pa alternating pressure. It can be seen that the voltage is very stable.

[0087] Example 2: Example 2 is similar to Example 1, except that the parameters in the preparation method are different, specifically including:

[0088] The method for preparing the polymer composite nanofiber membrane described in Example 2 comprises:

[0089] S1: Synthesis of ZnO nanoparticles: 5 g of zinc acetate dihydrate was dissolved in 20 ml of deionized water at 500 rpm using a magnetic stirrer at room temperature (27 ° C) for 60 minutes; then, 12 ml of NaOH 3M was added dropwise to the zinc acetate solution at 85 ° C to form an emulsion suspension with a pH of about 12.5, which was then allowed to stand until precipitation. The sediment was then washed until the pH was neutral; subsequently, the obtained sediment was heated at a temperature of 100 ° C for 60 minutes, and the formed ZnO nanoparticles were used for the next process.

[0090] S2: Preparation of ZnO / PAN nanofiber membrane: The synthesis of PAN@ZnO nanofibers was performed by electrospinning. The ZnO suspension solution was prepared by weighing 3.0 g PAN (polyacrylonitrile) and dissolving it in 20 g DMF, and weighing 0.30 g ZnO and dissolving it in 4 g DMF; then stirring at 1000 rpm for 100 minutes at a temperature of 60°C. The above two solutions were mixed, and then stirred at 400 rpm for 360 minutes at a temperature of 80°C to prepare the PAN / ZnO spinning solution, and the composite solution was injected into 4 5 ml syringe pumps, each with 2.5 ml. Then a 21G size syringe needle was installed on the syringe and connected horizontally to the positive terminal, so that the positive terminal tip (needle) and the aluminum collector plate (negative terminal) had a space of 13 cm. The injection rate was 10 uL / min, the voltage was 18 kV to 19 kV, and the needle was 13 to 15 cm away from the receiver. After the spinning process is completed, the spinning membrane is placed in a 60°C vacuum drying oven overnight to complete the curing and drying and remove the solvent contained in the fiber membrane, and then placed in a 60°C forced air drying oven for 12 hours to accelerate the volatilization of the solvent to obtain a PAN / ZnO spinning fiber membrane as a nano power generation layer 3; then it is hydrolyzed in a NaOH alcohol / water mixed solution for 0.5h to obtain a hydrophilic HPAN / ZnO nanofiber membrane, and this fiber membrane is used as a collection matrix in the subsequent preparation process;

[0091] S3: Preparation of nanosphere layer: that is, co-spinning method to prepare sandwich structure TENG: ZnO nanoparticles are mixed into (9wt%~11wt%) PVDF / DMF solution and stirred at 60℃ and 1000rpm for 60 minutes, PEG (1wt%) is added and then the solution is used as PVDF / ZnO electrostatic spray solution. After that, the synthesized layer 3 (PAN / ZnO fiber membrane) is used as the receiving substrate and electrostatically sprayed at 25℃ and 50% humidity to prepare the microsphere layer, with a push speed of 10μL / min, a voltage of 16kV~18kV, and a needle distance of 13~15cm from the receiver. After the electrostatic spraying is completed, it is immediately replaced with 14wt% ZnO / PVDF electrospinning precursor solution (the addition amount of ZnO is 0.5wt%) to spin layer 1. After completion, the spinning membrane is placed in a 60℃ vacuum drying oven overnight to complete curing and drying and remove the solvent contained in the composite membrane.

[0092] S4: Preparation of hydrophilic support layer by hot pressing: The support layer nanocomposite was prepared into a thin film by solution casting. An appropriate amount of PAN or PDMS powder was dissolved in N-methylpyrrolidone (NMP) solvent. At the same time, different amounts of CA (0.5wt%) were also dissolved in the solvent. The mixture was magnetically stirred in a 70°C water bath for 6 hours. It was then placed in a bath sonicator for 1 hour to eliminate bubbles. The mixture was cast on a smooth polytetrafluoroethylene petri dish and dried in an oven at 70°C for 1 hour to ensure the removal of the solvent. The solvent cast film was then further processed by hot pressing, and the film was subjected to a pressure of 10MPa at 90°C and hot pressed for 2 minutes.

[0093] Preparation of the hydrophobic support layer: dissolving polytetrafluoroethylene powder in a solvent, and preparing a thin film by a flat coating method, a tape casting method, a solution casting method, or a melting method to obtain a hydrophobic support layer;

[0094] S5: Lamination preparation of composite membrane: A textile electrostatic flow guide net is used and laminated with a nanofiber composite membrane to obtain a sandwich-structured nano-power generation composite membrane.

[0095] Example 3: Example 3 is similar to Example 1, except that the parameters in the preparation method are different, specifically including:

[0096] The method for preparing the polymer composite nanofiber membrane described in Example 3 comprises:

[0097] S1: Synthesis of ZnO nanoparticles: 5 g of zinc acetate dihydrate was dissolved in 30 ml of deionized water at 1000 rpm using a magnetic stirrer at room temperature (27°C) for 60 minutes; then, 12 ml of NaOH 3M was added dropwise to the zinc acetate solution at 95°C to form an emulsion suspension with a pH of about 13.5, which was then allowed to stand until precipitation. The sediment was then washed until the pH was neutral; subsequently, the obtained sediment was heated at a temperature of 110°C for 60 minutes, and the formed ZnO nanoparticles were used for the next process.

[0098] S2: Preparation of ZnO / PAN nanofiber membrane: The synthesis of PAN@ZnO nanofibers was performed by electrospinning. A ZnO suspension solution was prepared by weighing 4.0 g PAN (polyacrylonitrile) and dissolving it in 30 g DMF, and weighing 0.40 g ZnO and dissolving it in 6 g DMF; then stirring at 1000 rpm for 140 minutes at a temperature of 60°C. The above two solutions were mixed, and then stirred at 600 rpm for 360 minutes at a temperature of 80°C to prepare a PAN / ZnO spinning solution, and the composite solution was injected into 4 5 ml syringe pumps, each with 2.5 ml. Then a 21G size syringe needle was installed on the syringe and connected horizontally to the positive terminal, so that the positive terminal tip (needle) and the aluminum collector plate (negative terminal) had a space of 13 cm. The injection rate was 10 uL / min, the voltage was 18 kV to 19 kV, and the needle was 13 to 15 cm away from the receiver. After the spinning process is completed, the spinning membrane is placed in a 60°C vacuum drying oven overnight to complete the curing and drying and remove the solvent contained in the fiber membrane, and then placed in a 60°C forced air drying oven for 12 hours to accelerate the volatilization of the solvent to obtain a PAN / ZnO spinning fiber membrane as a nano power generation layer 3; then it is hydrolyzed in a NaOH alcohol / water mixed solution for 0.5h to obtain a hydrophilic HPAN / ZnO nanofiber membrane, and this fiber membrane is used as a collection matrix in the subsequent preparation process;

[0099] S3: Preparation of nanosphere layer: that is, co-spinning method to prepare sandwich structure TENG: ZnO nanoparticles are mixed into (9wt%~11wt%) PVDF / DMF solution and stirred at 80℃ and 1000rpm for 60 minutes, PEG (1wt%) is added and then the solution is used as PVDF / ZnO electrostatic spray solution. After that, the synthesized layer 3 (PAN / ZnO fiber membrane) is used as the receiving substrate and electrostatically sprayed at 25℃ and 50% humidity to prepare the microsphere layer, with a push speed of 10μL / min, a voltage of 16kV~18kV, and a needle distance of 13~15cm from the receiver. After the electrostatic spraying is completed, it is immediately replaced with 14wt% ZnO / PVDF electrospinning precursor solution (the addition amount of ZnO is 2wt%) to spin layer 1. After completion, the spinning membrane is placed in a 60℃ vacuum drying oven overnight to complete curing and drying and remove the solvent contained in the composite membrane.

[0100] S4: Preparation of hydrophilic support layer by hot pressing: The support layer nanocomposite was prepared into a thin film by solution casting. An appropriate amount of PAN or PDMS powder was dissolved in N-methylpyrrolidone (NMP) solvent. At the same time, different amounts of cellulose acetate CA (2wt%) were also dissolved in the solvent. The mixture was magnetically stirred in a 70°C water bath for 6 hours. It was then placed in a bath sonicator for 1 hour to eliminate bubbles. The mixture was cast on a smooth polytetrafluoroethylene petri dish and dried in an oven at 70°C for 1 hour to ensure the removal of the solvent. The solvent cast membrane was then further processed by hot pressing, and the membrane was subjected to a pressure of 10MPa at 100°C and hot pressed for 2 minutes.

[0101] Preparation of the hydrophobic support layer: dissolving polytetrafluoroethylene powder in a solvent and preparing it into a thin film by a flat coating method, a tape casting method or a solution casting method to obtain a hydrophobic support layer;

[0102] S5: Lamination preparation of composite membrane: A textile electrostatic flow guide net is used and laminated with a nanofiber composite membrane to obtain a sandwich-structured nano-power generation composite membrane.

[0103] The amount of ZnO added to the ZnO / PVDF electrospinning precursor solution in step S3 of the above-mentioned embodiments 1-3 of the present invention was used as a variable control to test the change of the β-crystalline content of the PVDF fiber membrane with the amount of doped ZnO. The results are as follows: Figure 7 As shown, Figure 7 It shows that the β-phase content is the highest at 1wt% ZnO doping, reaching 80.3%.

[0104] In the description of the present application, the description with reference to the terms "one embodiment", "some embodiments", "in the present embodiment", "specific example", or "some examples" etc. means that the specific features, mechanisms, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, mechanisms, materials or characteristics described may be combined in a suitable manner in any one or more embodiments or examples. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0105] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A method for preparing a polymer composite nanofiber membrane, characterized in that: The following steps are involved: S1: Preparation of ZnO nanoparticles: NaOH is added dropwise to a zinc acetate solution to form an emulsion suspension, the emulsion suspension is allowed to stand until the emulsion suspension is precipitated, the precipitate is extracted and washed to neutrality, and then the precipitate is heated to obtain ZnO nanoparticles; S2: Preparation of ZnO / PAN nanofiber membrane: dissolving polyacrylonitrile in N,N-dimethylformamide solution to obtain polyacrylonitrile solution, dissolving ZnO nanoparticles in N,N-dimethylformamide solution, stirring to obtain ZnO nanoparticle solution, then mixing the polyacrylonitrile solution and the ZnO nanoparticle solution to obtain a ZnO suspension solution, using the ZnO suspension solution as a spinning solution for electrospinning, and after spinning, curing the obtained spinning membrane and further removing the solvent to obtain a ZnO / PAN nanofiber membrane; S3: Preparation of nano power generation layer: adding the ZnO nanoparticles to the PVDF / DMF solution and stirring, further adding polyethylene glycol to the stirring solution to obtain an electrostatic spray solution, using the ZnO / PAN nanofiber membrane prepared in step S2 as a receiving substrate, electrostatically spraying the electrostatic spray solution on the receiving substrate to obtain a nano-microsphere layer, and after the electrostatic spraying is completed, replacing the electrostatic spray solution with a ZnO / PVDF electrospinning precursor solution, and performing electrostatic spinning to obtain a nano power generation layer with a sandwich structure; S4: Preparation of a hydrophilic support layer: PAN or PDMS powder is dissolved in a solvent, cellulose acetate is added and mixed, and then a membrane is formed by electrospinning to obtain a hydrophilic support layer; Preparation of the hydrophobic support layer: dissolving polytetrafluoroethylene powder in a solvent and preparing it into a thin film by a flat coating method, a tape casting method or a solution casting method to obtain a hydrophobic support layer; S5: Lamination to prepare composite membrane: stack the hydrophilic support layer, micro-sodium electrode layer, nano-power generation layer, hydrophobic support layer and micro-sodium electrode layer in this order and add adhesive, and prepare a polymer composite nanofiber membrane after hot pressing and lamination; the micro-sodium electrode layer is an electrode layer with micro-nano electrodes.

2. The method for preparing the polymer composite nanofiber membrane according to claim 1, characterized in that: In the step S1, the step of adding NaOH dropwise to the zinc acetate solution comprises: adding NaOH with a concentration of 3M dropwise to the zinc acetate solution at a temperature of 85-95°C; the pH of the emulsion suspension is 12.5-13.5; the preparation method of the zinc acetate solution comprises: dissolving zinc acetate dihydrate in deionized water at room temperature at a speed of 500-1000 rpm for 60 minutes to obtain a zinc acetate solution, and the mass ratio of the zinc acetate dihydrate to the deionized water is 5:(20-30).

3. The method for preparing the polymer composite nanofiber membrane according to claim 1, characterized in that: In the step S1, the condition for heating the precipitate is: heating the precipitate at a temperature of 100-110° C. for 60 minutes.

4. The method for preparing the polymer composite nanofiber membrane according to claim 1, characterized in that: In the step S2, in the polyacrylonitrile solution, the mass ratio of polyacrylonitrile to N,N-dimethylformamide solution is (3-4):(20-30); the stirring conditions for obtaining the ZnO nanoparticle solution after stirring are: stirring at a speed of 1000 rpm at a temperature of 60°C for 100-140 minutes, and the mass ratio of ZnO nanoparticles to N,N-dimethylformamide solution is (0.3-0.4):(4-6).

5. The method for preparing the polymer composite nanofiber membrane according to claim 1, characterized in that: In the step S2, the conditions for mixing and stirring the polyacrylonitrile solution and the ZnO nanoparticle solution are: stirring at a temperature of 80°C and a speed of 400-600rpm for 360 minutes; the conditions for the electrostatic spinning include: a space of 13cm between the tip of the positive terminal and the negative terminal, an injection speed of 10uL / minute, a voltage of 18-19kV, and a needle tip distance of 13-15cm from the receiver; the conditions for further removing the solvent after the solidification include: placing the spinning membrane in a 60°C vacuum drying oven overnight after the spinning process is completed to complete the solidification and drying, and then placing the spinning membrane in a 60°C forced air drying oven for 12 hours to accelerate the volatilization of the solvent and remove the solvent.

6. The method for preparing a polymer composite nanofiber membrane according to claim 1, characterized in that: In the step S2, after obtaining the ZnO / PAN nanofiber membrane, the step of hydrolyzing the ZnO / PAN nanofiber membrane is further included, including: hydrolyzing the ZnO / PAN nanofiber membrane in a NaOH alcohol / water mixed solution for 0.5-2h to obtain a hydrophilic HPAN / ZnO nanofiber membrane.

7. The method for preparing a polymer composite nanofiber membrane according to claim 1, characterized in that: In the step S3, the stirring condition is stirring at a temperature of 60-80°C and a speed of 1000rpm for 60 minutes; the conditions for the electrostatic spraying are: electrostatic spraying is performed at a temperature of 25°C and a humidity of 50%, and the injection speed is 10μL / min, the voltage is 16-18kV, and the needle is 13-15cm away from the receiver; after obtaining the sandwich structure nano power generation layer, the step also includes placing the nano power generation layer in a 60°C vacuum drying oven overnight to complete curing and drying and remove the solvent contained in the composite film; in the ZnO / PVDF electrospinning precursor solution, the amount of ZnO added is 0.5% to 2wt% of the total mass of the solvent.

8. The method for preparing a polymer composite nanofiber membrane according to claim 1, characterized in that: In the step S4, in the preparation of the hydrophilic support layer, the solvent is N-methylpyrrolidone solvent, and the amount of cellulose acetate added is 0.5% to 2wt% of the solvent; and after the mixing is carried out, it also includes: magnetically stirring the mixture in a 70°C water bath for 6 hours, then placing it in a bath ultrasonicator for 1 hour, and then casting the mixture on a smooth polytetrafluoroethylene culture dish and drying it in an oven at 70°C for 1 hour; the conditions for preparing the cast film by the hot pressing method are: applying a pressure of 10MPa at 90-100°C and hot pressing it for 2 minutes.

9. A polymer composite nanofiber membrane, characterized in that: The polymer composite nanofiber membrane is prepared by the preparation method of the polymer composite nanofiber membrane according to any one of claims 1 to 8, and the polymer composite nanofiber membrane includes a hydrophilic support layer, a micro-sodium electrode layer, a nano power generation layer, a hydrophobic support layer, and a micro-sodium electrode layer arranged in sequence from bottom to top, and the polymer composite nanofiber membrane is prepared by stacking the above-mentioned layers in sequence through a lamination process.

10. An application of a polymer composite nanofiber membrane, characterized in that: The application includes applying the polymer composite nanofiber membrane described in claim 9 to a mask.

Citation Information

Patent Citations

  • Electrostatic spinning nanofiber membrane as well as preparation method thereof

    CN103437071A

  • Preparation method of one-way wet conduction nano-fiber multilayer composite membrane with wettability gradient

    CN107059251A

  • Nanofibre lithium-ion battery separator with composite structure and preparation method therefor

    WO2013159752A1

  • Full-fiber electret generator-based highly efficient protective mask and preparation method therefor

    WO2021098480A1

Cited By

  • Composite hydrophobic fiber membrane based on friction nano-generator and preparation method of composite hydrophobic fiber membrane

    CN120625262A

  • A composite hydrophobic fiber membrane based on a friction nanogenerator and a preparation method thereof

    CN120625262B